2018
DOI: 10.1111/pace.13275
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of left ventricular endocardial pacing in advanced heart failure: Clinically efficacious but at what cost?

Abstract: LV endocardial lead implantation is a potentially efficacious alternative to CS lead placement, but preliminary data suggest a potentially higher risk of stroke during follow-up when compared to the expected incidence of stroke in similar cohorts of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(239 reference statements)
0
9
0
Order By: Relevance
“…Most studies demonstrated significant improvements in LV remodeling and favorable clinical response to CRT; however, its procedural complexity and substantial long-term thromboembolic risk limit wider adoption. [16][17][18][19] The ALSYNC (Alternate Site Cardiac Resynchronization) was the first multicenter trial of LV endocardial transvenous lead pacing (superior transvenous atrial transseptal approach), which enrolled 138 patients who either had a failed transvenous CS lead or had nonresponse to CRT. 20 The procedure was successful in 118 of the 132 attempted cases (89%).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies demonstrated significant improvements in LV remodeling and favorable clinical response to CRT; however, its procedural complexity and substantial long-term thromboembolic risk limit wider adoption. [16][17][18][19] The ALSYNC (Alternate Site Cardiac Resynchronization) was the first multicenter trial of LV endocardial transvenous lead pacing (superior transvenous atrial transseptal approach), which enrolled 138 patients who either had a failed transvenous CS lead or had nonresponse to CRT. 20 The procedure was successful in 118 of the 132 attempted cases (89%).…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial LV lead placement of CRT has become a routine procedure to improve symptoms and reduce mortality in selected HF patients . To our knowledge, this was the first study on CHF patients evaluating the effect of endocardial biventricular pacing on various locations of the heart on TDR homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern around delivery of lead-based endocardial LV pacing remains the risk of thromboembolic complications and the need for long-term anticoagulation. The overall stroke rate reported in one meta-analysis was 3.3–4.2 per 100 patient years, which is significantly higher than reported rates in equivalent heart failure trial populations [ 27 ]. Other concerns include the risk of impairment of and adhesion to the mitral valve by the transseptal lead and the risk associated with infected leads, as left-sided vegetations can lead to systemic embolic complications, and extraction of endocardial LV leads may be more complicated than right-sided leads.…”
Section: Lead-based Left Ventricular Endocardial Pacingmentioning
confidence: 95%
“…Other evidence for lead-based endocardial LV pacing is largely restricted to small single-center case series, and is summarized in two recent meta-analyses that included 362 and 384 patients, respectively [ 27 , 28 ]. In addition to the transseptal interatrial approach used in the ALSYNC trial, transseptal interventricular and transapical approaches to the LV have also been reported.…”
Section: Lead-based Left Ventricular Endocardial Pacingmentioning
confidence: 99%
See 1 more Smart Citation